Aspects Of Art, The Mystical Story And Religiosity Of Rangda And Barong In Mamintar Ceremony In The Adat Village Of Serangan - I Nyoman Yoga Segara (Mudra Jurnal Seni Budaya, 2016)
This article is a summary of the result of research to review aspects of the art, mystical stories and religiousity ofBarong and Rangda in Mamintar ceremony at Indigenous Village of Serangan. To reveal these aspects deeply, a qualitative approach is used with an ethnographic design through active participation observation, interview and documentation method. Based on this methodology, the research explained that ï¬rst, Barong and Rangda for Serangan people has an arts aspect but religious. This religious art is needed to bind a sense of devotion to God. Second, aspects of religious art in the Barong and Rangda were born from a long process of sanctification, including the magical power that is built through various myths and mystical stories. Third, Barong and Rangda is the meeting of two different strengths into one or monodualistic of a samyoga to generate new energy. Mamintar ceremony is samyoga of monodualistic Barong and Rangda with the energy produced to neutralize the negative influences that come from the sea. Fourth, the presence of Barong and Rangda in Mamintar ceremony becomes legitimator to the reinforcement of social solidarity of the society that are under the threat, especially from the outside through a giantic project of beach reclamation, strengthening selfidentity as an island communities who still love the sea, and means of culture to be in harmony with the universe.Keywords: Religious-Art, Mystical Stories, Religiosity, Barong, Rangda, Mamintar Ceremony.